Clinical characteristics and long-term outcomes of 12 children with vitamin D-dependent rickets type 1A: A retrospective study - Lin, Yunting; Guan, Zhihong; Mei, Huifen; Zhang, Wen; Zhou, Zhizi; Su, Ling; Cheng, Jing; Zheng, Ruidan; Liang, Cuili; Cai, Yanna; Yin, Xi; Wu, Dongyan; et al. (Frontiers in Pediatrics, 2022)
Purpose Vitamin D-dependent rickets type 1A (VDDR1A) is a rare autosomal recessive disorder caused by deficiency of the CYP27B1 gene. This study aims to investigate the phenotypic and genotypic features of VDDR1A children in southern China and evaluate the long-term therapeutic effects. Methods Twelve children from southern China with VDDR1A were enrolled in this study. Their clinical, radiological, biochemical, and molecular findings were analyzed retrospectively. The rickets severity score (RSS), biochemical parameters, and height standard deviation score (HtSDS) were used to evaluate clinical outcomes. Results Six males and six females were included in this VDDR1A cohort. The age of onset was from 6 months to 1.8 years, and the age at diagnosis was 2.1 ± 0.8 years. The most common clinical symptoms at diagnosis were delayed walking (10/12) and severe growth retardation (9/12). HtSDS at diagnosis was negatively associated with age (p < 0.05). All patients presented with hypocalcemia, hypophosphatemia, increased serum alkaline phosphatase and parathyroid hormone, and high RSS at diagnosis. Two allelic variants of the CYP27B1 gene were identified in all patients, including nine different variants, four known and five novel, with c.1319_1325dupCCCACCC(p.Phe443Profs*24) being the most frequent. All patients were treated with calcitriol and calcium after diagnosis, and all patients but one were followed-up from 6 months to 15.6 years. HtSDS, RSS, and biochemical parameters were found to be improved during the first few years of the treatment. However, only five patients had good compliance. Although RSS and biochemical parameters were significantly improved, the HtSDS change was not significant from the time of diagnosis to the last visit, and seven patients remained of a short stature (HtSDS < −2). Conclusion Our study extends the mutational spectrum of VDDR1A and finds a hotspot variant of the CYP27B1 gene in southern China. The results reconfirm the importance of early diagnosis and treatment compliance and reveal the challenge of height improvement in VDDR1A patients.